Enhancing the economic value and consumer preferences of commercial mondol stingray (Himantura gerardi) leather creative products - Sahubawa, Latif; Pertiwiningrum, Ambar; Rahmadian, Yudi (2017)
The research objectives were to design, assess the economic value and consumer preference level of stingray leather products. The research method included a product design, analysis of economic value and consumer preferences. Mondol stingray (Himantura gerardi) leather, with a length of 50 cm and width of 30 cm, were processed into ID card wallet, man and women’s wallet and key holder. The number of respondents involved to analyze the preference level is 75 respondents (students, lecturers and employees of Universitas Gadjah Mada). Indicators of consumer preferences were model, color, price and purchasing power. The price of ID card wallet is Rp. 450,000; women wallet is Rp. 650,000 and a key holder is Rp. 300,000. Consumer preferences on ID card wallet were as follow: 84 % stated very interesting model; 83 % stated very interesting color; 61 % stated cheap and 53 % had enough. Consumer preferences of women’s wallet were as follow: 81 % stated very interesting model; 84 % stated very interesting color; 56 % stated cheap and 57 % had enough. Consumer preferences on key holder were as follow: 49 % stated interesting model; 72 % stated very interesting color; 61 % stated cheap and 57 % had enough.